Interstitial lung disease in rheumatoid arthritis: an update on diagnosis and management. (June 2012) - Malik, Saadia; Saravanan, Vadivelu; Kelly, Clive
There has been increasing recognition of the importance of respiratory disease in patients with rheumatoid arthritis (RA) over the last 5 years. Interstitial lung disease (ILD) is the only complication of RA increasing in prevalence and accounts for approximately 6% of all RA deaths, with a mean survival of just 3 years following diagnosis in several historic series. Clinically significant ILD is present in approximately 3–5% of all RA patients, making RA-ILD a common and potentially fatal disorder. Although the presence of RA-ILD increasingly influences therapeutic decision-making, our understanding of its pathogenesis remains limited, as is the evidence base to guide therapeutic intervention. Recent data suggests that RA-ILD may relate to smoking and/or the presence of CCP antibodies. High-resolution computed tomography has allowed clarification of the type and extent of pulmonary involvement without recourse to lung biopsy in most cases. Moreover, the use of certain therapeutic agents may be contraindicated in patients with RA-ILD, while latest figures suggest that the prognosis of the condition has improved with the introduction of newer therapeutic agents.